Gamete competence assessment by polarizing optics in assisted reproduction - Montag, Markus; Köster, Maria; Ven, Katrin van der; Ven, Hans van der (Human reproduction update, 2011)
The purpose of this study was first to give an overview of the historical development of polarization microscopy, second to describe the various applications of this technique in assisted reproduction techniques (ART) and third to discuss the potential benefit of polarization microscopy as a predictor for IVF success.The history of polarization microscopy was undertaken by performing a backward search in the scientific literature using Google and internet sites of several Societies for Microscopy and Cell Biology. Studies of polarization microscopy in ART were identified by using a systematic literature search in PubMed and Scopus.A total of 62 articles were identified by the direct search and further relevant articles were found by screening the cited literature in these articles. The topics relevant for assisted reproduction were spindle and zona imaging in combination with IVF success, meiotic cell cycle progression, pharmaceutical studies and cryopreservation. A separate topic was the use of sperm birefringence in ART.The majority of studies are observational studies and were not performed in a randomized manner and there is no direct comparison of techniques using other gamete selection markers. Despite this, most studies show that polarization microscopy may help us to further increase our knowledge on gametes and meiosis. Whether certain applications such as spindle or zona imaging may lead to an increase in IVF success is unclear at present. Publications on the use of polarization microscopy on sperm are still very limited.
Gesehen am 07.09.2022